Kamus kosakata bahasa inggris untuk anak / Runna Aulia; penyunting, Ardhika Verdianata; ilustrasi, Rizky Amelia Putri - RUNNA AULIA; Rizky Amelia Putri; Ardhika Verdianata (Cakrawala, 2014)
112 hlm. : ilus. ; 26 cm.